A New 4-D Hyperchaotic System with Four-Scroll Hidden Attractor, Its Properties and Bifurcation Analysis - Mustafa, Mamat; Dolvis, L.G; Vaidyanathan, S.; Jacques, K; Sambas, A.; Sukono, . (2019)
This paper announces a new four-dimensional hyperchaotic system with a four-scroll attractor and discusses its dynamic properties such as Lyapunov exponents, phase portraits, Kaplan-Yorke dimension and equilibrium points. Our calculations show that the new hyperchaotic system has no equilibrium point and hence it exhibits hidden attractor. Our new hyperchaotic system has three nonlinearities in total. A detailed bifurcation analysis has been presented for the new hyperchaotic system with four-scroll hidden attractor. Specifically, we discussed bifurcation analysis such as route to four-scroll hyperchaos, coexisting bifurcation, multistability, two parameter Lyapunov exponents and antimonotonicity.